Formation of Social Conservation Characters Through Examples in Folklore for Male/Female Students - Luthfi, Asma; Mustofa, Mohammad Solehatul; Fatimah, Nurul (Universitas Negeri Semarang, 2024)
The existence of folklore in society is one of the local wisdom that has content value that can be to form character conservation social . Folk tales in general transmitted through tradition oral or tradition speak from word of mouth passed from one person to another through stories . As time goes by sophistication technology information , tradition oral Already seldom found in game children. Games child moment This Already Lots replaced with gadget ( smart phone ) with various application online games in it . This is causing folklore to become more reduce told and already not popular anymore among people children and teenagers . As happened in the Village Mangusanri , Semarang City, children and teenagers Already many do not know folklore and the values contained in it . One of the efforts made to introduce back to folklore or folklore is​ hold a program devotion with socialization and practice models direct in folklore narrative for children . Group target from activity devotion This is students / female students of TPQ Al Ikhlas Kelurahan Mangunsari , The implementation methods used in this community service program are socialization, Focus Group Discussion (FGD), and training/simulation. With this program, the community service group target It is hoped that they can be fostered, empowered and independent so that the goals are achieved . from the community service program This can achieved.